Influence of abrupt increase in relief and the flow pattern in CD nozzle. (2022) - Ridwan,; Suheel, J.I.; Delvi, Hamza Afser; Khan, Sher Afghan; Faheem, Mohammed
Abstract: In this investigation, experiments are done for Mach 1.25, 1.3, 1.48, 1.6, and 1.8 for different duct lengths and the nozzle pressure ratio to evaluate the microjets' control effectiveness for a duct diameter ratio of 2.5 to assess the influence microjets as dynamic control on the flow field in the duct and efficiency of the control. These Mach numbers are selected as the base drag will maximum at transonic low low supersonic Mach numbers. The NPRs selected are such that the flow will be over, under, and perfectly expanded and how dynamic control responses under these level of expansion. The results indicate that the flow pattern in the pipe is matching for most of the instances. However, the results are shown only for combining parameters with a discrepancy in the stream pattern due to a stream management mechanism. The results show no definite trend, and control results in both positive and negative trends inside the duct flow field. The control efficacy is a resilient function of NPR. For lower NPRs, the minimum duct requirement is 3D, but at higher NPR and lower Mach, the stream continued connected with the duct for 2D length. The marginal change in the inertia level does the flow pattern in the pipe.